Mexico's revolution then and now - Cockcroft, James D. (Monthly Review Press, 2010)
Written to commemorate the one hundredth anniversary of the first predominantly anti-capitalist revolution in the world, Mexico's Revolution Then and Now is the perfect introductory text and one that will also sharpen the understanding of seasoned observers. Cockcroft provides readers with the historical context within which the revolution occurred; explains how the revolutionary process has played out over the past ten decades; tells us how the ideals of the revolution live on in the minds of Mexico's peasants and workers; and critically examines the contours of modern Mexican society, includ.